Stop GnRH-agonist/GnRH-antagonist protocol: a different insight on ovarian stimulation for IVF - Raoul Orvieto (BMC, 2023)
Abstract Ovarian stimulation (OS) is one of the key factors in the success of in vitro fertilization-embryo transfer (IVF-ET), by enabling the recruitment of numerous healthy fertilizable oocytes and, thereby, multiple embryos. The Stop GnRH-agonist/GnRH-antagonist (GnRH-ag/GnRH-ant), which offers all the advantages of using long suppressive GnRH-ag, with GnRH-ant, is in my opinion a valuable addition to the armamentarium of OS protocols. It allows cycle programming, better follicular synchronization and offers successful outcome in a variety of challenging cases such as poor responders, Poseidon group 4 poor prognosis patients, those with elevated peak progesterone (P) serum levels, poor embryo quality or repeated IVF failures.